Development of a rapid diagnostic test for enterovirus-71 using an isothermal amplification based assay - Ratna Sri Dewi, Sedi (Universiti Malaysia Sarawak (UNIMAS), 2015)
An in-house nucleic acid sequence based amplification (NASBA) assay protocol for the detection of EV-A71 from both virus isolates and clinical specimens was developed in this study. A primer set, targeting the VP1 gene region, was designed and the sensitivity and specificity was tested using conventional RT-PCR and subsequently used in a NASBA assay. The detection of EV-A71 NASBA amplicons was successfully achieved using ethidium bromide-stained RNA agarose gel electrophoresis. The in-house EV-A71 NASBA protocol detected a panel of 54 of 60 EV-A71 virus isolates from different genogroups and subgenogroups and no cross-reactivity was observed against other EV serotypes. The NASBA assay was additionally evaluated on a panel of, 41 clinical specimens of various sample types from HFMD cases in Sarawak. Twenty-one (95.5%) of 22 clinical specimens that were confirmed to be EV-A71 positive by RT-PCR and virus isolation were successfully detected by the NASBA assay. The other 19 clinical specimens that were concordantly EV-A71 negative by both RT-PCR and virus isolation, were not detected by the EV-A71 NASBA assay. Verification of the EV-A71 NASBA amplicons from virus isolates and clinical specimens were successfully achieved by sequencing of the amplified region. In conclusion, the NASBA assay developed in this study provides a useful alternative for the screening and detection of EV-A71.